2015
DOI: 10.1002/smi.2637
|View full text |Cite
|
Sign up to set email alerts
|

Face it, don't Facebook it: Impacts of Social Media Addiction on Mindfulness, Coping Strategies and the Consequence on Emotional Exhaustion

Abstract: Addiction to social media has now become a problem that societies are concerned with. The aim of the present study is to investigate the impacts that social media addiction has on mindfulness and choice of coping strategy, as well as to explore the consequences on emotional exhaustion. The survey data were collected from 211 employees in 13 enterprises in Thailand. Results from partial least square structural equation modelling revealed that people who are highly addicted to social media tended to have lower m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(84 citation statements)
references
References 39 publications
4
71
3
6
Order By: Relevance
“…The slightly stress-protective effect of internet use contrasts with studies that have shown deleterious long-term effects of overuse of social media (Sriwilai and Charoensukmongkol 2016; Zheng and Lee 2016). However, the association in our data was at the momentary level: it can be summarized as “during internet use, there were fewer stressors” rather than “for people with more overall internet use, there were fewer stressors.” This is consistent with findings that social-media use can buffer acute stress (Rus and Tiemensma 2016).…”
Section: Discussioncontrasting
confidence: 70%
“…The slightly stress-protective effect of internet use contrasts with studies that have shown deleterious long-term effects of overuse of social media (Sriwilai and Charoensukmongkol 2016; Zheng and Lee 2016). However, the association in our data was at the momentary level: it can be summarized as “during internet use, there were fewer stressors” rather than “for people with more overall internet use, there were fewer stressors.” This is consistent with findings that social-media use can buffer acute stress (Rus and Tiemensma 2016).…”
Section: Discussioncontrasting
confidence: 70%
“…Social media has become a vital and integral part of peoples' lives in today's digital age. Although social media provides significant benefits in many aspects, it is crucial to understand the negative impacts that it causes as well (Sriwilai & Charoensukmongkol, 2016). Anxiety and depression are psychological states that a person can experience where there is a stressor(s) present.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, social media platforms were found to be to have no relationship with one's feeling of deep and meaningful social connectedness. Sriwilai & Charoensukmongkol (2016) found that those "who are addicted to social media may spend most of their time on their social media activities in order to help them forget about the problem that they are experiencing instead of trying to think about how to face the said problem" (p.433). Emotion-focused coping does not provide adequate coping, as it only allows individuals to divert their attention from stress temporarily (Chang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, mindfulness has been demonstrated to reduce mental health problems such as anxiety, depression, negative emotions, and loneliness [113,114] and increase well-being in self-esteem, life satisfaction, and positive emotions [114]. Moreover, researchers have reported a relationship between technology addiction and mindfulness, for example, social media addiction negatively impacts mindfulness Page 6087 [115]. Further, because individuals with higher levels of mindfulness utilize more adaptive coping strategies when faced with stressful events [114], these positive coping strategies enable them to modify the relationship with their addictive behavior and enhance their wellbeing [116].…”
Section: Mindfulness As a Mediatormentioning
confidence: 99%